Peningkatan Pemahaman Rencana Pemekaran Kecamatan di Kecamatan Pedurungan Kota Semarang - Arifin, Zaenal (Fakultas Hukum Universitas Semarang, 2022)
The Semarang City Government plans to expand the area, be it a sub-district or village area. The expansion of urban and sub-district areas in the city of Semarang has the aim of improving public services and welfare. The formation of a sub-district can be in the form of the expansion of 1 (one) sub-district into 2 (two) or more sub-districts, and/or the unification of village and/or sub-district areas from several sub-districts. In an effort to encourage regional development, a region is required to be able to increase regional original income, by exploring the potential of its resources for regional financing and to streamline the implementation of regional development, which in the end can be developed as a basic economic sector and superior economy that has competitiveness. in a competitive global economy. The implementation of this community service activity is in the form of increasing understanding in the juridical field to partners by providing socialization about the legal basis for regional expansion, and increasing understanding to partners with a sociological approach regarding sub-district expansion in Semarang City in order to minimize the impacts that will arise in the expansion of sub-district areas and provide socialization the purpose of regional expansion is to improve the welfare of the community. The results achieved from this activity of increasing understanding are an increase in understanding of increasing understanding of the division of sub-districts in the city of Semarang. From the results of the evaluation and measurement of questionnaires to participants, there was an increase in the understanding of partners by 76.19%. Abstrak Rencana Pemerintah Kota Semarang melakukan pemekaran wilayah baik itu wilayah kecamatan atau kelurahan. Pemekaran wilayah kelurahan dan kecamatan di kota Semarang mempunyai tujuan untuk meningkatkan pelayanan dan kesejahteraan masyarakat. Pembentukan kecamatan dapat berupa pemekaran 1 (satu) kecamatan menjadi 2 (dua) kecamatan atau lebih, dan/atau penyatuan wilayah desa dan/atau kelurahan dari beberapa kecamatan. Dalam usaha mendorong perkembangan wilayah, suatu daerah dituntut untuk dapat meningkatkan pendapatan asli daerah, dengan menggali potensi-potensi sumber daya yang dimiliki guna pembiayaan daerah serta mengefektifkan pelaksanaan pembangunan daerah, yang pada akhirnya dapat dikembangkan sebagai sektor ekonomi basis dan ekonomi unggulan yang memiliki daya saing dalam persaingan ekonomi global. Pelaksanaan kegiatan pengabdian masyarakat ini berbentuk peningkatkan pemahaman dalam bidang yuridis kepada mitra dengan memberikan sosialisasi tentang dasar hukum pemekaran wilayah, dan peningkatkan pemahaman kepada mitra dengan pendekatan sosiologis mengenai pemekaran kecamatan di Kota Semarang agar meminimalisir dampak-dampak yang akan timbul dalam pemekaran wilayah kecamatan dan memberikan sosialisasi tujuan dari pemekaran wilayah adalah untuk meningkatkan kesejahteraan masyarakat. Hasil yang dicapai dari kegiatan peningkatan pemahaman ini adalah adanya peningkatan pemahaman peningkatan pemahaman pemekaran kecamatan di Kota Semarang. Dari hasil evaluasi dan pengukuran kuesioner kepada peserta, maka ada peningkatan pemahaman dari mitra sebesar sebesar 76,19%.